The metaphorical representation of time in the poetry of Yolanda Westphalen - Cabrera Junco, Jaime (2021)
This article analyzes the metaphorical representation of the time in the poetry book Viviendo el tiempo (2008), by Yolanda Westphalen (1920-2011), an author is assigned to the generation of the 60s. For this analysis, we will rely on the study of Lakoff and Johnson, who in Metaphors We Live By consider that the language is a representation of everyday experience. The postulated by the Italian researcher Stefano Arduini in his work Prolegomena for a general theory of figures will provide us a theoretical support on the construction of the metaphor of time in some representative poems selected for this purpose.